2017
DOI: 10.3390/ijms18020271
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Fumarate Therapy Significantly Improves the Responsiveness of T Cells in Multiple Sclerosis Patients for Immunoregulation by Regulatory T Cells

Abstract: Multiple sclerosis (MS) is a chronic autoimmune disease caused by an insufficient suppression of autoreactive T lymphocytes. One reason for the lack of immunological control is the reduced responsiveness of T effector cells (Teff) for the suppressive properties of regulatory T cells (Treg), a process termed Treg resistance. Here we investigated whether the disease-modifying therapy of relapsing-remitting MS (RRMS) with dimethyl fumarate (DMF) influences the sensitivity of T cells in the peripheral blood of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Previous studies of this nature on other immune cell types demonstrated that DMF treatment resulted in a significant decrease in the frequency of B cells expressing IL-6, TNF-α and GM-CSF, and that DMF treatment improves the responsiveness of MS patients’ effector T cells to allogeneic regulatory T cells in vitro [14, 15]. In this study, we show that the amount of IL-6 produced by classically stimulated monocytes was significantly greater from RRMS subjects compared to HC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of this nature on other immune cell types demonstrated that DMF treatment resulted in a significant decrease in the frequency of B cells expressing IL-6, TNF-α and GM-CSF, and that DMF treatment improves the responsiveness of MS patients’ effector T cells to allogeneic regulatory T cells in vitro [14, 15]. In this study, we show that the amount of IL-6 produced by classically stimulated monocytes was significantly greater from RRMS subjects compared to HC.…”
Section: Discussionmentioning
confidence: 99%
“…To explore therapeutic strategies to overcome the resistance of effector T cells toward Treg-mediated suppression in multiple sclerosis (MS) patients, a humanized model based on newborn Rag2 −/− γ −/− mice engrafted with CD25-depleted PBMCs from different MS patients was applied (287). Transfer of gp120-activated Treg cells from healthy subjects into these mice prevented GvHD only when engrafted PBMCs were derived from MS patients that received disease-modifying therapy but not from those being therapy-naïve (287).…”
Section: The Challenge Of Translating Cell-based Therapies For Rheumamentioning
confidence: 99%
“…DMF-treated MS patients have demonstrated reduced immune cells, particularly CD4 + and CD8 + T lymphocytes (Longbrake et al, 2016). It can also recover effector T cells response to the inhibitory function of Treg (Schlöder, Berges, Luessi, & Jonuleit, 2017). Moreover, there is evidence implying that DMF induces apoptosis in activated T cells (Treumer et al, 2003).…”
Section: Significant Reduction Of Microglia and Macrophages And Presementioning
confidence: 99%